Establishment of a desert foundation species is limited by exotic plants and light but not herbivory or water. Issue 4 (7th August 2020) - Filazzola, Alessandro; Brown, Charlotte; Westphal, Michael; Lortie, Christopher J.
Abstract: Questions: The biodiversity of deserts is becoming increasingly threatened due to global change including the introduction of invasive species. Desert shrubs are foundational species that can facilitate native plant communities but can also benefit exotic species. The influence of exotic plants on the establishment of benefactors from seeds or seedlings is a critical knowledge gap. We tested if the establishment, survival, or growth of seedlings for a benefactor shrub species in California was reduced by the invasive grasses that they facilitate in the field. Location: San Joaquin Desert, California, USA. Methods: We conducted a field survey to determine if a native shrub, Ephedra californica, facilitated the invasive grass Bromus madritensis . Using seed collected from the field, we conducted a competition experiment on Ephedra californica, using a densities series of Bromus madritensis and under manipulated conditions of light, water, and simulated herbivory. We measured seedling establishment, survival, and biomass of Ephedra californica and Bromus madritensis. Results: In the field, Ephedra californica facilitated Bromus madritensis within the shrub canopy. In the competition experiment, Bromus madritensis had consistent negative effects on Ephedra californica emergence and seedling survival at all resource and herbivory levels. The emergence and survival of Ephedra californica was reduced in low light, but none of the manipulated conditions increased the competitive effect of Bromus madritensis. Conclusions: Reciprocal costs of facilitation by shrubs were evident in emergence and seedling survival but not in growth once established. Water, herbivory, and shade did not mitigate these costs, but also did not exacerbate competition from exotics. Direct competition with exotic plant species is the most significant impact tested here on dryland shrub species and manipulations of resources or herbivory may not effectively promote shrub recruitment. Native shrubs are well adapted to variable desert conditions and could be effective foundational species if invasive grasses are reduced. Abstract : Foundation shrubs can facilitate the biomass and abundance of exotic grasses. However, these grasses in turn compete with the shrubs and reduce the emergence and survival of shrub seedlings. We found this pattern to remain consistent regardless of manipulations to artificial grazing, water level, and shading.